Estudo da microbiota formadora de histamina em cavala (Scomberomorus cavalla) e avaliação da atividade bactericida de óleos essenciais - Carneiro, Ana Patrícia Cavalcante (2018)
Histamine is one of the products of fish microbial spoilage, can cause food poisoning, generally referred to as scombroid poisoning. The aim of this work was to isolate and identify histamine-producing bacteria (HPB) in the skin superficial mucus and gills of the mackerel (Scomberomorus cavalla) and to evaluate the use of substances with bioactive properties (essential oils) for the control of bacterial growth and, consequently, the formation of histamine. Four samplings (May to August of 2017) were carried out at Fish Market in Fortaleza-CE. The quantification of culturable heterotrophic bacteria (CHB) and HPB was performed. The interactions between the CHB and the HPB (total and halo) counts were analyzed among the four samplings through analysis of variance and Tukey's test (p≤0.05). The colonies with purple staining and halo in the differential medium for HPB (positive result for histamine production) were isolated for identification. The isolates were classified as morphotintorials and identified by molecular biology. The HPB were qualitatively evaluated for the ability to produce cadaverine and putrescine by decarboxylation of lysine and ornithine. The antimicrobial activity of rosemary, clove (buttons) and ginger essential oils was evaluated against the 20 identified and selected HPB strains. The counts for the mackerel skin surface were 4.52 Log CFU/cm2 for CHB, 4.67 Log CFU/cm2 for HPB (total) and 4.16 Log CFU/cm2 for HPB (purple and halo). For gills 5.53 Log CFU/gill for CHB, 6.8 Log CFU/gill for HPB (total) and 6.2 Log CFU/gill for HPB (purple and halo). There were 113 isolates of HPB, 99 (87.61%) Gram negative and 14 (12.39%) Gram positive. As for the diversity of HPB, the most abundant were Pseudomonas (36%), Vibrio (18%), Aeromonas (8%), Bacillus (4%) and Shewanella (4%). Of the 113 HPB, 57 (50.44%) are positive for the decarboxylation of lysine and ornithine, 6 (5.32%) for lysine, 15 (13.27%) for ornithine and 35 (30.97%) didn’t present a positive result. This research is a contribution to the knowledge of the diversity of HPB in tropical marine fish. CHB and HPB (with positive result) were quantified in equivalent amounts in the skin superficial mucus and in the gills of the mackerel. It was observed an influence of the time of year on the number and diversity of HPB, probably occurring due to the seasonality of the rainfall regime in the State of Ceará. Both HPB Gram negative and Gram positive are present on the mackerel skin surface and gills, but there is a predominance of Gram negative bacteria. Most of HPB was also able to produce putrescine and cadaverine. Clove essential oil was the most efficient as an antimicrobial against HPB.